2D Diluted Multiferroic Semiconductors upon Intercalation. (8th April 2019) - Tu, Zhengyuan; Wu, Menghao
Abstract: The direct combination of high‐mobility semiconductors and efficient multiferroic memories within the same material is desirable for integration of multifunctional electronics but remains a challenge. Stimulated by recent progress on intercalation of layered materials, first‐principles evidence of 2D room‐temperature multiferroicity in a series of doped metal dichalcogenides is shown, mainly focused on intercalated MoS2 and Bi2 Se3 . The intercalated ions may induce a switchable vertical polarization for high‐density recording as well as electrically tunable magnetism for highly efficient "electric writing + magnetic reading." Akin to diluted magnetic semiconductors, certain multiferroic regions can be selectively formed via such doping, which can be directly integrated in the high‐mobility semiconductor wafer like n / p doping channels. In particular, other intriguing properties such as topological superconductivity may also be endowed in ferroelectric metal Cux Bi2 Se3 . The bandgap of the intercalated systems can also be tuned via control of the doping density of ions, which may render a spatial‐varying bandgap for efficient light adsorption plus the enhanced exciton separation and open‐circuit voltage for ferroelectric photovoltaics. Abstract : The intercalation of transition‐metal ions can be a general approach to selectively induce multiferroicity by doping in certain domains of high‐mobility 2D semiconductors, which may induce a switchable vertical polarization for high‐density recording as well as electrical‐tunable magnetism for highly efficient "electric writing + magnetic reading."